SELECTION EFFECTS IN RICE AS ASSESSED BY GENETIC ANALYSIS IN SEGREGATING POPULATIONS - Ahmadikhah, Asadollah (Plant Breeding and Seed Science, 2018)
Estimation of selection effects on changes of a trait is of vital importance for the success of any plant breeding program, and helps to select the desirable breeding method. Heritability and genetic advance are important selection parameters, and selection success is a reflectance of selection response. To estimate selection effects on rice genetic parameters, a research was conducted using 4 different generations (two parents: Neda and Sadri, and two segregating populations: BC1F1 and BC1S1). After development of a backcross population, a single plant (BC1#4) was selected based on its desirable performance, particularly in heading date and seven other morphological traits. BC1F1 population compared to mid-parent performance showed advance for heading date, plant height, tiller number, hundred seed weight, weight of filled seeds per panicle and grain yield per plant, while mean performance of BC1F1 population compared to BC1S1 population showed advance only for heading date, plant height, tiller number and grain yield. Prevalence of additive genetic effects in controlling panicle weight, hundred seed weight, weight of filled seeds per panicle, plant height and heading date was observed, and in contrast prevalence of non-additive effects in controlling grain yield was observed. High general heritability was observed for most traits, while only heading date and plant height showed a considerable specific heritability (60.7% and 67.5%, respectively), and grain yield showed a relatively low specific heritability (37.0%). High expected genetic advance (ΔGe) was obtained for tiller number (49.4%), followed by grain yield (43.5%) and plant height (35.5%), while the highest real genetic advance (ΔGe) was obtained for heading date (-8.5%) and tiller number (5.4%). High selection success was obtained only for heading date (51.8%). Altogether, the obtained results gave promise for selecting progenies with early maturity and semi-dwarfism in early segregating generations, while they suggested preference of heterosis for improvement of grain yield.